Influencing factors and quantitative prediction of gas content of deep marine shale in Luzhou block - Xinyang He; Kun Zhang; Shu Jiang; Zhenxue Jiang; Xueying Wang; Wei Jiang; Jing Li; Yijia Wu; Zhi Gao; Tian Tang; Cheng Yang; Xuejiao Yuan; et al. (Scientific Reports)
Abstract The exploration and development of deep marine shale gas has made significant breakthroughs, but factors influencing gas contents of deep marine shale are elusive, and quantitative prediction methods of gas content needs to be refined urgently. In this study, the deep marine shale of Longmaxi Formation in Luzhou area was taken as an example, vitrinite reflectance analysis, kerogen microscopy experiment, TOC content analysis, mineral composition analysis, gas content measurement, isothermal adsorption experiment, physical property analysis and argon ion polishing scanning electron microscopy experiment were carried out to find out factors affecting the gas content of deep marine shale, and a gas content prediction model has been worked out. Conclusions below have been reached: the content of adsorbed gas is mainly affected by Ro, TOC content, porosity, water saturation, clay mineral content, formation temperature and pressure; the content of free gas is mainly controlled by porosity, water saturation, formation temperature and pressure; according to the prediction models, the adsorbed gas content, free gas content and total gas content of each well were quantitatively calculated, and the study area was divided into Class I (with a total gas content ≥ 11 m3/t), Class II (with a total gas content between 9 m3/t and 11 m3/t), and Class III (with a total gas content < 9 m3/t) gas-bearing areas.